Equal Access to Justice for Persons with Disabilities: A Comparative Legal Analysis of Indonesia and Australia under the CPRD - Syuib, M. (Universitas Islam Negeri Raden Intan Lampung, 2025)
Access to justice is a fundamental right for persons with disabilities, yet its realization remains challenging in many countries, including Australia and Indonesia. Both nations have ratified the Convention on the Rights of Persons with Disabilities (CRPD), committing to uphold disability rights across key areas such as legal reform, inclusive education, employment, social protection, and healthcare. However, practical implementation is hindered by inadequate resources, limited political will, persistent social stigma, and weak monitoring systems. This study compares how Australia and Indonesia interpret and apply the CRPD within their legal systems, aiming to identify lessons each country can learn from the other. Using a comparative, doctrinal legal research methodology supported by a qualitative, normative, and analytical approach. The study finds that while Australia offers more developed institutional mechanisms, it still faces accessibility issues in rural and Indigenous communities. Indonesia, meanwhile, struggles with enforcing existing laws and ensuring effective policy delivery. Despite having legal frameworks in place, both countries face ongoing barriers to practical access to justice for persons with disabilities. The study concludes that beyond legal commitments, comprehensive implementation, sustained funding, and intersectoral collaboration are essential to making the CRPD’s vision of equality and inclusion a lived reality. Mutual learning can help drive systemic improvements.